Creativity via a genre pedagogy to promote EFL indigenous students’ writing - Malini Ganapathy; Salasiah Che Lah; Jonathan Phan (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper presents a conceptual framework that has been developed to promote creativity among English as a Foreign Language (EFL) Malaysian indigenous students, specifically in the teaching of writing. The objectives are to introduce the factors that contribute to indigenous students’ low English proficiency, highlight writing challenges of indigenous students, propose a genre pedagogical framework as a means to address their writing challenges and simultaneously, motivate their learning via creative practices, and discuss past studies on the efficacy of a genrebased writing pedagogy that promotes creativity. This paper employed an integrative review approach in sourcing and critically analysing relevant literature. The framework was developed to address the educational challenges of primarily providing learning opportunities to the marginalised indigenous minority in Malaysia, the Orang Asli, which concurrently bridges the English language gap between urban and rural schools in the country. By conceptualising a genre as a model for teaching EFL writing through the integrated theoretical lenses of sociocultural learning as well as extensive secondary research, a framework for evaluating the potential of teaching genrebased EFL writing is derived, focussing on the creative aspect. Thus, this paper enhances understanding of the practicality of genre writing in addressing the writing challenges of low proficiency indigenous students. The proposed framework has the potential to serve as a reference point to other EFL teachers involved in teaching indigenous students globally.